1999
DOI: 10.1098/rspb.1999.0899
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of flying mimetic, passion–vine butterfliesHeliconius

Abstract: Wing-beat frequency and the degree of asymmetry in wing motion were more similar among mimics than among sister species of passion-vine butter£ies in the genus Heliconius. Asymmetry in wing motion is not attributed to lift production, and serves as the ¢rst clear example of a mimetic behavioural signal for a £ying organism. Because the similarities in wing motion are too subtle for humans to observe with the naked eye, they serve as a previously unexplored mimetic signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Mimicry complexes may also fail to converge because the established patterns are so distinct that predators would be very unlikely to confuse them (Turner 1983, p. 279), or the mutations required for switching between patterns are too large/numerous and therefore extremely rare (Turner 1976, p. 196;Sheppard et al 1985, p. 579). Finally, differences in size between mimicry complexes could help keep complexes from converging because size itself may play a role in predator discrimination, and size is correlated with morphological and kinematic traits shown to converge among mimetic butterflies (Hill unpublished;Srygley 1999;Srygley and Ellington 1999). Overall, it appears that mimetic diversity is maintained because establishment of new color patterns, and persistence and immigration of others, is balanced against selection for mimetic resemblance, only some of which is associated with habitat.…”
Section: Discussionmentioning
confidence: 90%
“…Mimicry complexes may also fail to converge because the established patterns are so distinct that predators would be very unlikely to confuse them (Turner 1983, p. 279), or the mutations required for switching between patterns are too large/numerous and therefore extremely rare (Turner 1976, p. 196;Sheppard et al 1985, p. 579). Finally, differences in size between mimicry complexes could help keep complexes from converging because size itself may play a role in predator discrimination, and size is correlated with morphological and kinematic traits shown to converge among mimetic butterflies (Hill unpublished;Srygley 1999;Srygley and Ellington 1999). Overall, it appears that mimetic diversity is maintained because establishment of new color patterns, and persistence and immigration of others, is balanced against selection for mimetic resemblance, only some of which is associated with habitat.…”
Section: Discussionmentioning
confidence: 90%
“…Heliconius is an extraordinarily diverse genus of long‐lived, toxic butterflies distributed from northern Argentina to southern United States (Brown 1981). They exhibit intra and interspecific color pattern diversity that together with habitat preferences and flight characteristics, often converge among species within the genus to form remarkable examples of mimicry (e.g., Brown 1981; Mallet and Gilbert 1995; Srygley and Ellington 1999; Estrada and Jiggins 2002). Antiaphrodisiac compounds are produced in glands located inside two chitinized claspers in the last abdominal segment in males (Eltringham 1925; Gilbert 1976; Schulz et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…If predators recognize the combination of traits as a mimetic signal, then they may select against the evolution of a single trait away from the local adaptive phenotype more strongly than concordant changes in all of the traits. Hence, wing coloration, wing-beat frequency and asymmetries in the wing motion (Srygley & Ellington 1999) may all have to change in concordance. If a higher wing-beat frequency is necessary to balance the body weight given the smaller wing length of the m^e co-mimics (Srygley 1999), then body mass may also have to change in concordance with the other traits.…”
Section: Discussion (A) Aerodynamic Power Requirements and Mimicrymentioning
confidence: 99%
“…Moreover, Srygley (1999) and Srygley & Ellington (1999) demonstrated that mimetic Heliconius butter£ies have similar £ight behaviours. Heliconius cydno and Heliconius sapho had lower wing-beat frequencies and a more asymmetrical wing motion due to a prolonged downstroke and shortened upstroke, whereas Heliconius melpomene and Heliconius erato had higher wing-beat frequencies and a nearsinusoidal wing motion with a more even downstroke and upstroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation